Mobile Augmented Reality application for Digital Storytelling in high school education - Bustos, Henrry (2024)
Since the beginning of the pandemic, high education has been significantly affected, due to the sudden change from in-person to remote mode, which has led to not all teaching methods adapting to this new modality. In this context, the storytelling technique, which in face-to-face mode is effective, in the remote mode presents significant deficiencies since it cannot be interacted with in a shared space and with objects between students and the teacher. In this situation, some applications are poorly adapted for high education to solve this lack, which leads us in this work to present the development of a mobile application as a complement to the teaching of high education with storytelling using augmented reality, which leads to improving how to tell stories between students and teachers in remote teaching using digital storytelling, supported with augmented reality, a more participatory and interactive way of telling stories.